Pertumbuhan Ekonomi melalui Pengembangan Sistem Keuangan Usaha Mikro, Kecil dan Menengah (UMKM) Makanan dan Minuman di Yogyakarta - Rosa Nikmatul Fajri (Owner : Riset dan Jurnal Akuntansi, 2022)
MSMEs in Yogyakarta have a financial system condition that still requires comprehensive improvement. The research model for literacy studies in finding general problems contained in the background and qualitative research methods with a descriptive approach that directly knows the real situation in the field. The sample is the financial system from Food and Beverage SMEs in Yogyakarta. This study uses observation and documentation methods and the data used are 1) primary data in online financial system framework and offline financial system framework in excel and 2) secondary data supporting data or reinforcing data obtained. The findings are a) food and beverage HPP is still in the form of an estimate so that the profits recorded in the financial system are not reflected properly, b) the calculation of employee salaries is not combined into a single financial system, c) the financial statements presented cannot be understood by the public, d) the financial system forgets the principle of integration between online and offline so that it is repeated in recording and e) the distribution of BEP does not project the truth. Suggestions are improving the existing financial system by including supporting factors and Data Management Principles such as the principles of integration and togetherness, accrual, up-to-date and sustainable in the new financial system. The results is the MSME data management principle has been fulfilled by the implementation of new financial system that will directly contribute to economic growth.